Dynamic of changes of lactoferrin content in rotavirus infection in children of early age - Abaturov A.E.; Stepanova Yu.Yu. (Medičnì Perspektivi)
The article presents data that characterize the content of lactoferrin in the oropharyngeal fluid and blood serum in infants during rotavirus gastroenteritis. The aim of this study was to identify patterns of influence of lactoferrin concentration in serum and oropharyngeal fluid on the severity of rotavirus infection in children in the acute phase and during reconvalescence period. The subjects were 57 infants with diagnosed rotavirus gastroenteritis This study found a link between the concentration of lactoferrin immunoprotective factors and severity of rotaviral enteritis. The published data and results of own research suggest about possibility of using lactoferrin concentration of oropharyngeal fluid as a marker of severity of rotavirus infection.